Preparation, structural development, and mechanical properties of microfibrillar composite materials based on polyethylene/polyamide 6 oriented blends - Dencheva, Nadya Vasileva (2010)
The preparation of microfibrillar composites (MFCs) based on oriented blends of polyamide 6 (PA6) and high-density polyethylene (HDPE) is described. By means of conventional processing techniques, the PA6 phase was transformed in situ into fibrils with diameters in the upper nanometer range embedded in an isotropic HDPE matrix. Three different composite materials were prepared through the variation of the HDPE/PA6 ratio with and without a compatibilizer: MFCs reinforced by long PA6 fibrils arranged as a unidirectional ply; MFCs containing middle-length, randomly distributed reinforcing PA6 bristles; and a nonoriented PA6-reinforced material in which the PA6 phase was globular. The evolution of the morphology in the reinforcing phase (e.g., its visible diameter, length, and aspect ratio) was followed during the various processing stages as a function of the blend composition by means of scanning electron microscopy. Synchrotron X-ray scattering was used to characterize selected unidirectional ply composites. The presence of transcrystalline HDPE was demonstrated in the shell of the reinforcing PA6 fibrils of the final MFCs. The impact of the compatibilizer content on the average diameter and length of the fibrils was assessed. The influence of the reinforcing phase on the tensile strength and Young’s modulus of the various composites was also evaluated.